(untitled) (Texas Journal of Medical Science, 2023)
Avascular necrosis of bones (osteonecrosis) has developed as a bad consequence of the COVID-19 (SARS-CoV-2) pandemic that has swept the world. In 5-58% of patients with the type of covid19 fertilizer, the bones were affected by avascular necrosis. In 39% of patients with SARS-CoV-2, avascular necrosis of the hip bone developed within a few months after atypical pneumonia. Avascular necrosis is a disease that often develops in people of working age (average age is 33-45 years) and leads to severe disability associated with the death of bone tissue in a particular area. Discussions about the pathogenesis of postcovid avascular necrosis, the possibility of its diagnosis and treatment in the early stages are subject to active discussion. Given that COVID-19 infection is common among young people and working-age people, early diagnosis and treatment of this form of osteonecrosis is of great social and economic importance